PSIKOEDUKASI REGULASI EMOSI UNTUK MENINGKATKAN KECERDASAN EMOSIONAL PADA SISWA SMK X - Anggraeni, Nadya Ferdhita; Sholichah, Ima Fitri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Emotional intelligence is a crucial competency for vocational high school students in managing academic demands, social interactions, and preparation for entering the workforce. Preliminary findings indicate that many students experience difficulties in recognizing, understanding, and regulating their emotions adaptively. This program aimed to enhance students’ emotional intelligence through emotion regulation psychoeducation delivered in three structured sessions, including emotional awareness, identification of emotional triggers and calming strategies, and management of negative thoughts and emotional responses. The program was implemented at SMK X and involved 31 eleventh-grade TKR students using an educational and participatory approach through learning modules, self-reflection, group discussions, and emotional skill exercises. Program effectiveness was evaluated using a pre-test and post-test design with an emotional intelligence assessment instrument. The results demonstrated an increase in the mean emotional intelligence score from 92.6 prior to the intervention to 101.8 following the intervention. N-Gain Score analysis revealed that most participants showed low to moderate improvement, while a small proportion achieved high improvement. Overall, emotion regulation psychoeducation positively contributed to students’ ability to recognize emotions, understand emotional triggers, and apply more constructive emotional management strategies. These findings suggest that psychoeducational interventions can serve as a practical preventive approach to fostering emotional intelligence and supporting a more adaptive, positive, and supportive school environment. ABSTRAKKecerdasan emosional merupakan kompetensi esensial bagi peserta didik Sekolah Menengah Kejuruan (SMK) dalam menghadapi tuntutan akademik, interaksi sosial, dan kesiapan memasuki dunia kerja. Temuan awal menunjukkan bahwa sebagian siswa masih mengalami kesulitan dalam mengenali, memahami, dan mengelola emosi secara adaptif. Program ini bertujuan meningkatkan kecerdasan emosional siswa melalui psikoedukasi regulasi emosi yang disusun dalam tiga sesi bertahap, meliputi pengenalan emosi, identifikasi pemicu serta strategi penenangan diri, dan pengelolaan pikiran serta respons emosional negatif. Kegiatan dilaksanakan di SMK X dengan melibatkan 31 siswa kelas XI TKR menggunakan pendekatan edukatif-partisipatif melalui modul pembelajaran, refleksi diri, diskusi kelompok, dan latihan keterampilan emosional. Evaluasi efektivitas program dilakukan menggunakan desain pre-test dan post-test dengan instrumen kecerdasan emosional. Hasil menunjukkan adanya peningkatan skor rata-rata kecerdasan emosional dari 92,6 sebelum intervensi menjadi 101,8 setelah intervensi. Analisis N-Gain Score mengindikasikan bahwa sebagian besar peserta mengalami peningkatan pada kategori rendah hingga sedang, sementara sebagian kecil mencapai kategori tinggi. Secara keseluruhan, psikoedukasi regulasi emosi berkontribusi positif dalam meningkatkan kemampuan siswa mengenali emosi, memahami pemicu, serta menerapkan strategi pengelolaan emosi secara lebih konstruktif. Program ini berpotensi menjadi intervensi preventif yang aplikatif untuk mendukung perkembangan sosial-emosional siswa dan menciptakan iklim sekolah yang lebih adaptif dan kondusif.